Geomorphic Response to Differential Uplift: River Long Profiles and Knickpoints From Guadalcanal and Makira (Solomon Islands) - Boulton, Sarah J. (Frontiers in Earth Science, 2020)
Knickpoints have long been recognised as key geomorphic features that can be used to reveal the landscape evolution of a region. In particular, mobile knickpoints resulting from relative base-level fall record a landscape in the process of change and can encode information about the timing and rate of landscape response. Here, digital elevation model analysis is undertaken to; a) identify topographic lineaments related to active faulting, and b) extract geomorphic metrics and document associated knickpoints for rivers on Guadalcanal and Makira (San Cristobal) part of the Solomon Island chain. These islands have been experiencing uplift of up to 2 mm/yr since at least the mid Holocene on the upper (Pacific) plate of the San Cristobal Trench of the Solomon Island Forearc. For Guadalcanal, 23 out of 53 studied rivers exhibit slope-break knickpoints, characteristic of base-level fall, and 27 new topographic lineaments with ~E-W orientation are identified. By contrast, on Makira 14 of 41 studied rivers have slope-break knickpoints, where the rivers are steeper below the knickpoint than above. In addition, 76 new lineaments are inferred, trending NE-SW and likely to be extensional faults. For both Guadalcanal and Makira there is a good correlation between knickpoint elevation/catchment area and distance upstream from the sea, and a weak correlation between relief and knickpoint elevation. There are no clear relationships between the knickpoints and the new topographic lineaments. These data indicate that both islands are undergoing active river incision caused by regional tectonic uplift along an active subduction zone. On Makira, river steepness (ksn) scales with uplift, and K, coefficient of erosion, is in the range 1 x 10-5 – 7 x 10-6 m0.1yr-1, while K can be estimated as 1 x 10-5 – 5 x 10-8 m0.1yr-1 for Guadalcanal. Calculation of K for steady-state rivers demonstrates a rock strength control on the fluvial response and highlights the importance of lithology on river evolution. Furthermore, the distinct landscape response of the two islands supports the hypothesis that there are different arc segments present along the Solomon Arc and suggests that the Holocene uplift rates for Guadalcanal may not be representative of long-term uplift.